2014
DOI: 10.4088/jcp.13m08914
|View full text |Cite
|
Sign up to set email alerts
|

Latent Trajectories of Trauma Symptoms and Resilience

Abstract: The results confirm earlier findings of stress response heterogeneity following military deployment and highlight the impact of predeployment, perideployment, and postdeployment risk factors in predicting PTSD symptomatology and late-onset PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 0 publications
8
62
0
Order By: Relevance
“…A general analysis of the response rates showed no significant differences between soldiers who answered before, at homecoming and 2.5 years after homecoming (Danish Defence, 2013). Further, previous analyses have found no differences between the latent growth mixture modelling (LGMM) model established based on the 561 individuals included here and one including only those responding four or more times (Andersen et al, 2014). Further descriptive information on the measurements at pre-deployment, after homecoming and post-deployment from this study is shown in Table 1.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…A general analysis of the response rates showed no significant differences between soldiers who answered before, at homecoming and 2.5 years after homecoming (Danish Defence, 2013). Further, previous analyses have found no differences between the latent growth mixture modelling (LGMM) model established based on the 561 individuals included here and one including only those responding four or more times (Andersen et al, 2014). Further descriptive information on the measurements at pre-deployment, after homecoming and post-deployment from this study is shown in Table 1.…”
Section: Methodsmentioning
confidence: 70%
“…The PCL has been validated in this sample of Danish soldiers against the Structured Clinical Interview for Axis I disorders of the DSM-IV (SCID-I) (First, Spitzer, Gibbon, & Williams, 2002; Karstoft, Andersen, Bertelsen, & Madsen, 2014). In this sample it showed high internal consistency ( α  = 0.94) (Andersen et al, 2014). The civilian version of the PCL was used to allow the respondents to report PTSD symptoms related to any traumatic events and not only symptoms caused by military experiences.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The last decades have seen a plethora of research on the toll of recent wars in Iraq and Afghanistan (Andersen, Karstoft, Bertelsen, & Madsen, 2014; Carlson et al, 2010; McDevitt-Murphy et al, 2010; Ramchand et al, 2010; Schnurr et al, 2010; Shea, Vujanovic, Mansfield, Sevin, & Liu, 2010). Many studies have aimed at estimating the prevalence of PTSD following deployment and have reported greatly varying rates.…”
Section: Introductionmentioning
confidence: 99%